Developing patient-orientated Barrett's oesophagus services: the role of dedicated services. Issue 1 (22nd February 2022) - Ratcliffe, Elizabeth; Britton, James; Hamdy, Shaheen; McLaughlin, John; Ang, Yeng
Abstract : Introduction: Barrett's oesophagus (BO) is common and is a precursor to oesophageal adenocarcinoma with a 0.33% per annum risk of progression. Surveillance and follow-up services for BO have been shown to be lacking, with studies showing inadequate adherence to guidelines and patients reporting a need for greater disease-specific knowledge. This review explores the emerging role of dedicated services for patients with BO. Methods: A literature search of PubMed, MEDLINE, Embase, Emcare, HMIC, BNI, CiNAHL, AMED and PsycINFO in regard to dedicated BO care pathways was undertaken. Results: Prospective multicentre and randomised trials were lacking. Published cohort data are encouraging with improvements in guideline adherence with dedicated services, with one published study showing significant improvements in dysplasia detection rates. Accuracy of allocation to surveillance endoscopy has been shown to hold cost savings, and a study of a dedicated clinic showed increased discharges from unnecessary surveillance. Training modalities for BO surveillance and dysplasia detection exist, which could be used to educate a BO workforce. Qualitative and quantitative studies have shown patients report high levels of cancer worry and poor disease-specific knowledge, but few studies have explored follow-up care models despite being a patient and clinician priority for research. Conclusions: Cost–benefit analysis for dedicated services, considering both financial and environmental impacts, and more robust clinical data must be obtained to support this model of care in the wider health service. Greater understanding is needed of the root causes for poor guideline adherence, and disease-specific models of care should be designed around clinical and patient-reported outcomes to address the unmet needs of patients with BO.